Status of Management of drinking water in rural zones of Cartago, Costa Rica - Soto-Córdoba, Silvia M. (2016)
In Costa Rica, almost 95 % of its urban population is benefited with public water services of good quality, because providers are supported on technology, human resources and financial resources. On the other hand, in rural zones water is distributed through aqueducts managed by associations of volunteers (named ASADA). This study focuses on rural aqueducts in Cartago, in rural areas. It verifies their actual conditions and the environmental problems originated from their operation, with the main purpose of setting technical improvements that will ensure a sustainable water service. The case study focus on the Cartago Province. The small ASADAs have the main operation and management problems.